Regional cortical white matter reductions in velocardiofacial syndrome: a volumetric MRI analysis - Kates, Wendy R; Burnette, Courtney P; Jabs, Ethylin W; Rutberg, Julie; Murphy, Anne M; Grados, Marco; Geraghty, Michael; Kaufmann, Walter E; Pearlson, Godfrey D (Biological psychiatry (1969), 2001)
Background: Velocardiofacial syndrome, caused by a microdeletion on chromosome 22q.11, is associated with craniofacial anomalies, cardiac defects, learning disabilities, and psychiatric disorders. To understand how the 22q.11 deletion affects brain development, this study examined gray and white matter volumes in major lobar brain regions of children with velocardiofacial syndrome relative to control subjects. Methods: Subjects were ten children with velocardiofacial syndrome and ten age- and gender-matched unaffected children. Coronal images were acquired with a 3-D spoiled gradient echo series and partitioned into 124, 1.5-mm contiguous slices. A stereotaxic grid was used to subdivide brain tissue into cerebral lobes, which were segmented into gray, white, and CSF compartments using an algorithm based on intensity values and tissue boundaries. Nonparametric statistics were used to compare lobar volumes of gray and white matter. Results: Analyses indicated that children with velocardiofacial syndrome had significantly smaller volumes in nonfrontal, but not frontal, lobar brain regions. Volume reductions affected nonfrontal white matter to a greater extent than nonfrontal gray matter. Conclusions: The presence of white matter reductions may be related to disturbances in myelination or axonal integrity in velocardiofacial syndrome. Further work is required to delineate the nature and extent of white matter anomalies, and to link them to variation in the neurocognitive and neuropsychiatric phenotype of velocardiofacial syndrome.